Evaluasi Kinerja Sistem Jaringan Irigasi Daerah Irigasi Bertais - Yunita Aprilina; Muhammad Faisal Karo-karo (Universitas Islam Al-Azhar, 2019)
ABSTRAK Kata kunci : evaluasi kinerja, jaringan irigasi, daerah irigasi Bertais. ABSTRACT Bertais Irrigation Area is an irrigation area located in Sandubaya Subdistrict of Mataram City with an area of 354.74 ha of raw land, consisting of residential land with an area of 269.17 ha, potential land of 14.70 ha and functional land with an area of 70, 87 ha. The area of agricultural land in the Bertais Irrigation Area is declining due to land conversion without prioritizing geographical conditions which are physical factors with their carrying capacity over a long period of time that will affect the quality and quantity of the environment. This study used observational methods on each indicator and assessment to evaluate the performance of irrigation networks. The indicators assessed were physical infrastructure, planting productivity, supporting facilities, personnel organization, documentation, and P3A institutions. This is based on the Minister of Public Works and Public Housing Regulation No. 12/PRT/M/2015 concerning Exploitation and Maintenance of Irrigation Networks. The results showed that the performance of irrigation networks for physical infrastructure reached a percentage value of 19.14% still below the specified minimum value of 25%, plant productivity was 1.61%, Supporting facilities with a percentage value of 1.21% below a minimum value of 5%, personnel organizations with a percentage value of 3.90% under a minimum value of 7.5%, documentation with a percentage value of 2% under a minimum value of 5%, and P3A with a percentage value of 2.15% below a minimum value of 5%. The total of the six indicators is 27.12%. The results of this assessment indicate that the performance of the Bertais irrigation network is poor so the recommendation for handling it is to rehabilitate the Bertais irrigation network. Keywords: performance evaluation, irrigation network, Bertais irrigation area.